PENGARUH JENIS DAN KONSENTRASI NUTRISI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) SECARA HIDROPONIK WICK SYSTEM) - Eka Widiyawati; Ramdan Hidayat; Didik Utomo Pribadi (UPN VETERAN JAWA TIMUR, 2018)
Lettuce (Lactuca sativa L.) classified in compositae family (Asteracea). The genetic source of lettuce derived from America and West Asia, whereas in Indonesia this plant growing so fast as commercial vegetable plant. Lettuce cultivation system that done by Indonesian farmers commonly is conventional. The efforts to increase productivity and quality of lettuce are conventionally hydroponic with wick system through testing of Type and Concentration of Nutrition. This research was held on February – March in Green house of Agriculture Faculty of UPN “Veteran” East Java. This study as factorial experiment 2 factor composed in Complete Random Design (CRD) and repeated 3 times. The first factor is the type of nutrition and the second factor is the concentration of nutrition, results showed there is no real interaction in all observation variables which include: number of leaves, length of the plant, large of leave, fresh weight and dry weight. Nutrition type give real effect on fresh weight, dry weight, and large of leave of the lettuce plant. AB Mix nutrition resulting in highest fresh weight and large of leaves and real different with Riyant nutrition. Concentration treatment unaffected in whole observation changes of growth and lettuce production.